2016
DOI: 10.1039/c6ra20999h
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic oxidation of ammonia over MnOx–TiO2 mixed oxides

Abstract: The formation of Mn–O–Ti and a high dispersal of Mn2O3 promoted oxygen activation and NH3 adsorption. The formation of N2O depends on temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…For example, in the ammonia oxidation process, the introduction of oxygen defects can promote the adsorption and dissociation of molecular oxygen to form active oxygen species. [ 50 , 51 ] The oxygen deficient perovskite shows superior activity and durability toward HER than pristine perovskite due to the increased oxygen defects, high‐degree of structure distortion and appropriate hydrogen absorption ability. [ 44 , 52 , 53 ] As the partial substitution of nickel with low‐valent copper and the annealing process in Ar, more oxygen vacancies may be formed in the crystalline lattice and attributed to the superior activities of LNCO55‐Ar.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the ammonia oxidation process, the introduction of oxygen defects can promote the adsorption and dissociation of molecular oxygen to form active oxygen species. [ 50 , 51 ] The oxygen deficient perovskite shows superior activity and durability toward HER than pristine perovskite due to the increased oxygen defects, high‐degree of structure distortion and appropriate hydrogen absorption ability. [ 44 , 52 , 53 ] As the partial substitution of nickel with low‐valent copper and the annealing process in Ar, more oxygen vacancies may be formed in the crystalline lattice and attributed to the superior activities of LNCO55‐Ar.…”
Section: Resultsmentioning
confidence: 99%
“…First, NH 3 reacts with atomic oxygen to form imide species (NH), and then NH is oxidized by atomic oxygen to form nitrosyl species (HNO). The N 2 O is subsequently formed by the reaction with two HNO (2HNO → N 2 O + H 2 O). ,, …”
Section: Resultsmentioning
confidence: 99%
“…12,13,30,31 For the S2 catalyst, there was not the peak of NO formation in the range of test temperatures, suggesting that the possible pathway of N 2 O formation on the S2 catalyst was different from that on the S1 catalyst. Song et al 20 have found that, for the MnO x -TiO 2 catalyst, N 2 O was formed by combining two nitrosyl species when the temperature was lower than 250 °C. Thus, the N 2 O formation on the S2 catalyst might follow the imide mechanism.…”
Section: Energy and Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platinum, palladium, rhodium, and silver are the catalysts with high activity. , For the catalysts of Pd, Rh, and Pt supported on Al 2 O 3 or ZSM-5, the NH 3 oxidation temperatures were 200–350 °C, whereas their N 2 selectivities were relatively low, typically less than 80% . Considering high cost of noble metals, transition metal oxides, such as MnO 2 , Fe 2 O 3 , CuO, Co 3 O 4 , NiO, V 2 O 5 , and MoO 3 , have attracted much attention. , These catalysts show high N 2 selectivities but require higher operation temperatures (typically 300–500 °C). ,, Song et al reported that a MnO x (0.25)-TiO 2 catalyst synthesized by the sol–gel method exhibited high performance; the NH 3 removal rate reached 100% at 200 °C, and the operating temperature window for a N 2 selectivity greater than 80% was 180–300 °C. Gora-Marek et al showed that a Fe 2 O 3 /ZSM-5-P catalyst synthesized by a 2-fold ion-exchange method achieved a N 2 selectivity of 90% at 475 °C, with the temperature for the NH 3 removal rate of 50% ( T 50 ) being 400 °C.…”
Section: Introductionmentioning
confidence: 99%